2005
DOI: 10.1128/aem.71.10.6308-6318.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Geochemical Heterogeneity in an In Situ Uranium Bioremediation Field Site

Abstract: The geochemistry and microbiology of a uranium-contaminated subsurface environment that had undergone two seasons of acetate addition to stimulate microbial U(VI) reduction was examined. There were distinct horizontal and vertical geochemical gradients that could be attributed in large part to the manner in which acetate was distributed in the aquifer, with more reduction of Fe(III) and sulfate occurring at greater depths and closer to the point of acetate injection. Clone libraries of 16S rRNA genes derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
302
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 216 publications
(326 citation statements)
references
References 40 publications
21
302
3
Order By: Relevance
“…Overall, our Winchester findings replicated the earlier results of Geobacter-like sequences being enriched in the groundwater phase while uranium reduction occurred (1,2). However, different…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our Winchester findings replicated the earlier results of Geobacter-like sequences being enriched in the groundwater phase while uranium reduction occurred (1,2). However, different…”
Section: Resultssupporting
confidence: 90%
“…These Geobacter-like clones were found to diminish as the system approached sulfate reduction during continued acetate amendment (1). Likewise, a similar injection experiment in 2003, replicated uranium reduction during biostimulation with enrichment of Geobacter-like clones in groundwater (approx 75%) and sediment samples (<10%), suggesting differences between microbial populations in groundwater and soil particles (2). These reports indicated that Geobacter-like microbes responded positively to acetate utilization and may be important in uranium reduction.…”
Section: Introductionmentioning
confidence: 68%
“…1). Samples from each core were collected and dried anaerobically and analyzed for both acid volatile sulfide (AVS) and Fe(II)/Fe(III) content, as described elsewhere (30).…”
Section: Sediment Sampling and Analysismentioning
confidence: 99%
“…However, Shewanella has not been found to be a prevalent DMRB during biostimulation at contaminated sites (9,17,18). For example, subsurface ethanol amendments enriched populations of DMRB and DSRB at Oak Ridge, TN.…”
Section: Introductionmentioning
confidence: 99%